Quality Prioritization in Wheat Flour Bagging Using FTA and FMEA: Prioritas Kualitas dalam Pengantongan Tepung Terigu Menggunakan FTA dan FMEA - Alvianto, Dwi Tio; Aryanny, Enny (Academia Open, 2026)
General Background: Quality control in food manufacturing is essential to maintain product consistency, reduce operational losses, and sustain customer trust, particularly in critical packaging stages such as wheat flour bagging. Specific Background: PT X recorded an average defect rate of 4.03% in the 25 kg wheat flour bagging process during January–December 2025, exceeding the company’s minimum defect target of 0.8%, with dominant defects including sewing failure, inappropriate weight, missed label installation, and torn packaging. Knowledge Gap: The existing quality control system in the bagging stage had not yet applied a structured root cause analysis and risk prioritization approach to determine the main sources of defects and corrective priorities. Aims: This study aims to analyze defects in the 25 kg wheat flour bagging process and determine improvement priorities using Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA). Results: FTA results showed defect probabilities of 0.0509% for sewing failure, 0.0405% for inappropriate weight, 0.0352% for missed label installation, and 0.0273% for torn packaging. Human, machine, and method factors were identified as the main causes of defects. FMEA results indicated that sewing failure caused by suboptimal detection systems had the highest Risk Priority Number (RPN) of 560, followed by weighing system disturbances and label inspection issues. Novelty: This study integrates FTA and FMEA to systematically identify defect probability and rank corrective priorities in wheat flour bagging operations. Implications: The findings support preventive maintenance scheduling, sensor checking, calibration routines, inspection checkpoints, and standardized operating procedures to reduce defects and improve bagging quality performance. Highlights: Sewing defects showed the highest defect probability and the most critical risk ranking. Human, machine, and method factors were identified as dominant root causes of production failure. Preventive maintenance and standardized inspection procedures were prioritized for corrective action. Keywords: Bagging, Fault Tree Analysis, Failure Mode and Effect Analysis, Quality Control.